Dependence of the performance of the reclaiming sewer cleaner with rigid guides from interchangeable bucket tools capabilities - Kh. A. Abdulmazhidov (Овощи России, 2022)
Relevance. Cleaning of reclamation channels is a very relevant event. The need to clean the canals and maintain them in working condition becomes obvious during the flood period, when it is necessary to remove excess water. The paper presents mathematical models for determining the performance of the PP-303 canal cleaner, a feature of which is the rectilinear movement of the bucket on rigid guides along the bottom along the axis of the canal to be cleaned.Methods. The article is formed on the basis of experimental research methods. The research was carried out based on experimental and calculated data. A network of drainage canals of the drainage system was taken as the research object, and the working equipment of the canal cleaner was taken as the research subject. Performance, which is the amount of products produced by the machine per unit of time, can be of three types (theoretical, technical, and operational) and can be determined with consideration of the design parameters of the working equipment. During the operation of trench cutting machines, their performance directly depends on the main parameter, namely, the depth of the canal being built; in the case of canal cleaning with canal cleaners, this parameter cannot be considered as the main one. This is due to the fact that siltation and sediments accumulating on the bottom and slopes of the canals during the operation of the reclamation system are extremely unevenly distributed along the length of the canal. The highest concentration and amount of sediments and siltation is observed mainly at the mouth of the canals, the junctions of canals of different levels, and the junctions of the drainage with the drainage canal. In this case, the most significant parameter is the thickness of the chips removed from the bottom and slopes of the canal by the bucket.Results. The results of the research showed that the performance of the channel cleaner, as a batch machine, is influenced by the very design of the working equipment, the main element of which is a bucket capable of moving in a straight line along rigid guides at different speeds. With obvious high values of the performance of continuous channel cleaning machines, it can be concluded that the channel cleaner RR-303 showed high values of technical and operational characteristics, mainly due to the use of a trapezoidal profile bucket.